The Plastic Glial-Synaptic Dynamics within the Neuropil: A Self-Organizing System Composed of Polyelectrolytes in Phase Transition - Fernandes de Lima, Vera Maura; Pereira, Alfredo (Wiley, 2016)
Several explanations have been proposed to account for the mechanisms of neuroglial interactions involved in neural plasticity. We review experimental results addressing plastic nonlinear interactions between glial membranes and synaptic terminals. These results indicate the necessity of elaborating on a model based on the dynamics of hydroionic waves within the neuropil. These waves have been detected in a small scale experimental model of the central nervous system, the in vitro retina. We suggest that the brain, as the heart and kidney, is a system for which the state of water is functional. The use of nonlinear thermodynamics supports experiments at convenient biological spatiotemporal scales, while an understanding of the properties of ions and their interactions with water requires explanations based on quantum theories. In our approach, neural plasticity is seen as part of a larger process that encompasses higher brain functions; in this regard, hydroionic waves within the neuropil are considered to carry both physiological and cognitive functions.